SEXINFO: A Sexual Health Text Messaging Service for San Francisco Youth - Levine, Deborah (American Public Health Association, 2008)
In response to rising gonorrhea rates among African American youth in San Francisco, Calif, Internet Sexuality Information Services, Inc, in partnership with the San Francisco Department of Public Health, developed SEXINFO, a sexual health text messaging service. SEXINFO is an information and referral service that can be accessed by texting “SEXINFO” to a 5-digit number from any wireless phone. A consortium of community organizations, religious groups, and health agencies assisted with identifying culturally appropriate local referral services. We conducted focus group sessions among youth aged 15 to 19 years to discuss the viability of the service. Usage of the service has been greater than expected, and an initial evaluation to assess the impact of SEXINFO on increasing access to sexual health services among at-risk adolescents has had promising results.